Analisis Dan Perancangan Ui/Ux Web Application Batavianet Dengan Metode Design Thinking - Septian Odie Saputra; Febrio Hasta Pratama; Eko Sudrajat (GLOBAL SCIENTS PUBLISHER, 2026)
The Enterprise Resource Planning (ERP) system plays a crucial role in integrating various business processes. Batavianet is an ERP system used by PT CAB, but there are still some issues in the User Interface (UI) and User Experience (UX) aspects. This study aims to analyze and redesign the UI/UX of the Batavianet web application using the Design Thinking method. Data were collected through observation, interviews, and questionnaires involving 15 users. Based on user needs analysis, a prototype was designed with modules grouped by division (Finance & Accounting, Purchase, Building Management) and a responsive interface for both mobile and web devices. The prototype was tested using the System Usability Scale (SUS), resulting in an average score of 81, categorized as acceptable, grade scale B, and adjective rating Good. The study demonstrates that the Design Thinking approach is effective in enhancing user satisfaction and ease of use of the ERP system.